Fabrication And Characterization Of Porous Alumina - Darong, Chhor (2013)
Porous alumina have been widely used in engineering applications. In this study, porous alumina has been fabricated using polymeric sponge and slip casting methods. In polymeric sponge method (using polyurethane sponge (PU)), type of binders (polyvinyl alcohol (PVA), wheat starch (WS) and tapioca starch (TS)), solid loadings (50, 60, and 70 wt. %), sintering temperatures (1200, 1300, 1400 and 1500 oC) and slurry recoating technique were studied. In slip casting method, polyvinyl alcohol (PVA) has been used as a binder and pore former, and the effect of solid loadings (50, 60, 70 and 75 wt. %) and sintering temperatures (1200, 1300, 1400 and 1500 oC) were studied. Results showed that porous alumina produced by slip casting method consisted of closed pores, pore size in ther range of 78 to 300 μm and higher compressive strength (1.22- 42.79 MPa). Whereas, porous alumina produced by polymeric sponge consisted of interconnected pores, pore size in the range of 800 μm to 1.5 mm and higher percentage of porosity (77.66 to 95 %). However, using recoating technique, it showed the compressive strength of the samples was improved. In conclusion, porous alumina produced by polymeric sponge method in this study has a potential to be used as hot gas filtration, whereas; porous alumina produced by slip casting method has a potential use as a catalysis.